Factors influencing secondary school students to pursue accounting program at tertiary level education in Malaysia - Yusri, Yusniyati; Ooi, Chun Yao; Senik, Rosmila; Mahyuddin, Nor Irdawati (Inlight Publisher, 2022)
The accounting profession in Malaysia is facing problem where the demand for accountants is higher than the number of accountants produced. The accounting education need to be nurtured from the early stage of education. The objective of this study is to investigate factors influencing students’ intention to choose accounting as their major academic program after graduating from secondary/high school. 113 questionnaires were collected from secondary school students in Northern Region of Malaysia. Using a Theory of Planned Behavior, the result show that attitude towards accounting program (ATT), subjective norm (SN) and perceived behavior control (PCB) have significant positive relationship with students’ intention to enroll in accounting program. To increase numbers of accountants in the industries, the government through Ministry of Education (MOE) should pay more attention and collaborating with professional bodies, audit firm and higher-level education institution in motivating secondary school students and create positive perception toward accounting courses and fields among them.